2007
DOI: 10.1121/1.2764467
|View full text |Cite
|
Sign up to set email alerts
|

Low-frequency modulation of distortion product otoacoustic emissions in humans

Abstract: Low-frequency modulation of distortion product otoacoustic emissions (DPOAEs) was measured from the human ears. In the frequency domain, increasing the bias tone level resulted in a suppression of the cubic difference tone (CDT) and an increase in the magnitudes of the modulation sidebands. Higher-frequency bias tones were more efficient in producing the suppression and modulation. Quasi-static modulation patterns were derived from measuring the CDT amplitude at the peaks and troughs of bias tones with various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
23
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 53 publications
8
23
0
Order By: Relevance
“…Previous studies have attempted to use the amplitude of the DPOAEs as indicators of cochlear function ͑Rebillard and Lavigne-Rebillard 1992; Kossowski et al, 2001;Kujawa and Liberman, 2001;Garner et al, 2008;Olzowy et al, 2008͒, reporting complex changes in the DPOAEs that were difficult to interpret, particularly as changes in the OP were not taken into consideration. Furthermore, other studies have taken similar approaches to investigate hearing function in humans ͑Mrowinski et al, 1996; Hensel et al, 2007;Bian andScherrer, 2007͒ andanimals ͑Frank andKössl, 1996;Lukashkin and Russell, 2002;Bian, 2004;Sirjani et al, 2004;Salt et al, 2005͒ and have reported similar relationships between pressure in the ear canal, the OP, and the amplitude of the DPOAEs as those reported here. However, this study is the first to directly relate the OP obtained from CM recordings to the OP derived solely from simultaneously recorded DPOAEs.…”
Section: Discussionsupporting
confidence: 64%
“…Previous studies have attempted to use the amplitude of the DPOAEs as indicators of cochlear function ͑Rebillard and Lavigne-Rebillard 1992; Kossowski et al, 2001;Kujawa and Liberman, 2001;Garner et al, 2008;Olzowy et al, 2008͒, reporting complex changes in the DPOAEs that were difficult to interpret, particularly as changes in the OP were not taken into consideration. Furthermore, other studies have taken similar approaches to investigate hearing function in humans ͑Mrowinski et al, 1996; Hensel et al, 2007;Bian andScherrer, 2007͒ andanimals ͑Frank andKössl, 1996;Lukashkin and Russell, 2002;Bian, 2004;Sirjani et al, 2004;Salt et al, 2005͒ and have reported similar relationships between pressure in the ear canal, the OP, and the amplitude of the DPOAEs as those reported here. However, this study is the first to directly relate the OP obtained from CM recordings to the OP derived solely from simultaneously recorded DPOAEs.…”
Section: Discussionsupporting
confidence: 64%
“…The ear-canal acoustic signal was recorded using a software developed in LabVIEW (v.8, National Instruments, NI) similar to previously described (Bian and Scherrer, 2007). Briefly, a 1s long bias tone with 10ms onset/offset ramps and a 0.1s flat tail (Fig.…”
Section: B Signal Processing and Data Acquisitionmentioning
confidence: 99%
“…These manipulations of cochlear mechanics are consistent with the consequences of modulating a saturating nonlinear system which could be attributed to the OHC transduction. Quantifying the cochlear transducer function (F Tr ) using DPOAEs can provide a noninvasive means for acquiring information of cochlear mechanics which is critical for possible clinical applications (Bian and Scherrer, 2007). Since the SOAEs may reflect the inner ear mechanical activities below or at hearing threshold where the cochlear transducer gain is highest, it is hypothesized that biasing the cochlear partition could reduce the gain and thus modulate the SOAE magnitudes.…”
Section: Introductionmentioning
confidence: 99%
“…Genuine three-tone DPs have been recognized and observed in their own right, both as "additional DPs" (in widely separated primaries) and as "sidebands" around one stimulus tone (when the other two primaries were close; e.g., Kemp and Brown 1986;Kemp 1998). They have also occurred as the spectral side-effect of low-frequency biasing of two-tone DPOAEs (Bian and Scherrer 2007;Marquardt et al 2007) or dynamic suppression of stimulus frequency OAEs (Meenderink and van der Heijden 2010). Unlike previous work, the aim of the present study was to integrate three-tone DPOAEs into a unifying framework alongside conventional DPOAEs.…”
Section: Discussionmentioning
confidence: 99%
“…The few studies that did address three-tone DPOAEs merely pointed out their occurrence (Kemp and Brown 1986;Kemp 1998), or analyzed them in the narrow context of low-frequency biasing (Bian and Scherrer 2007;Marquardt et al 2007) or time-varying suppression (Meenderink and van der Heijden 2010). It occurred to us that there is no a priori reason for such constraints, and that the systematic study of multitone (92) emissions may enlarge the scope of DPOAE research beyond what is possible with tone pairs.…”
Section: Introductionmentioning
confidence: 99%